SAT0669 DISCRIMINANT ABILITY OF THE PARENT VERSION OF THE JUVENILE ARTHRITIS DISEASE ACTIVITY SCORE IN A LARGE MULTINATION COHORT OF PATIENTS WITH JUVENILE IDIOPATHIC ARTHRITIS. (June 2019) - Ridella, Francesca; Januskeviciute, Giedre; Trincianti, Chiara; Giancane, Gabriella; Alongi, Alessandra; Vilaiyuk, Soamarat; Chédeville, Gaëlle; Pruunsild, Chris; Lahdenne, Pekka; Ruperto, Nicolino; Ravelli, Angelo; Consolaro, Alessandro; et al.
Abstract : Background: The assessment of disease activity plays a pivotal role in the management of children with juvenile idiopathic arthritis (JIA). Most recent recommendations require that parents' and children's perception is incorporated in the evaluation of the disease course and of effectiveness of therapeutic interventions. A new disease activity tool, named parent Juvenile Arthritis Disease Activity Score (parJADAS) and based only on parent-centered outcome measures, is currently under development (1). Objectives: To demonstrate, in a large multinational dataset of JIA patients, the discriminant ability of the parJADAS. Methods: The parJADAS includes 4 measures: 1) parent assessment of disease activity; 2) assessment of pain intensity; 3) proxy assessment of joint disease; 4) assessment of morning stiffness (MS). Disease activity and pain are assessed on a 21-numbered circle VAS (0 = best and 10 = worst). The active joint count is based on the count of any swollen or painful joint, irrespective of its type, up to a maximum of 10 joints. MS duration is assessed on a Likert scale, ranging from no MS (0 points) to > 2 hours of MS (10 points). Validation was conducted on a dataset of 8, 656 children with JIA from 49 countries, enrolled in the study of Epidemiology, treatment and Outcome of Childhood Arthritis (2), who had all the variables included in the parJADAS available. Discriminant ability was evaluated by comparing parJADAS levels (median, [IQR]) among patients with inactive disease (ID), low disease activity (LDA), moderate disease activity (MDA), and high disease activity (HDA) according to the cJADAS10; patients in remission, continued activity, or flare according to the attending physician; patients whose parents were satisfied or not with current disease state. To assess the possible influence of the articular and extra-articular damage on the parJADAS, the levels of the score in patients with or without damage (Juvenile Arthritis Damage Index > 0) were compared. For this analysis, only subjects in inactive disease and with at least 2 years of disease course were considered (n = 2, 423). Results: The levels of parJADAS in patients in ID, LDA, MDA, and HDA were 0.0 [0.0, 1.0], 3.0 [1.0, 6.0], 6.0 [2.0, 11.5], an 14.5 [8.5, 21.0], respectively (Kruskal-Wallis test, p < 0.001). The levels of par JADAS in patients in remission, continued activity, or flare according to the attending physician were 0.5 [0.0, 3.5], 9.0 [3.5, 17.0], 12.0 [5.5, 20.0], respectively (Kruskal-Wallis test, p < 0.001). Median parJADAS in patients whose parents were satisfied or not satisfied with disease course is 1.5 [0.0, 7.0] and 13.0 [6.6, 20.5], respectively (Mann-Whitney test p < 0.001). ParJADAS was not different in JIA patients in remission with or without damage measured with the JADI (Mann-Whitney test p = 0.08) Conclusion: The parJADAS showed excellent discriminate ability in a large multinational cohort. The score did not show to be relevantly influenced by disease damage in JIA patients in remission. References: [1] Consolaro A, et al. "Development and Initial Validation of the Parent and Child Versions of the Juvenile Arthritis Disease Activity Score". Arthritis Rheumatol. 2016; 68 (suppl 10). [2] Consolaro A, et al. "Phenotypic variability and disparities in treatment and outcomes of childhood arthritis throughout the world: results from an observational cohort study". The Lancet Child and Adolescent Health, In press. Disclosure of Interests: Francesca Ridella: None declared, Giedre Januskeviciute: None declared, Chiara Trincianti: None declared, Gabriella Giancane: None declared, Alessandra Alongi: None declared, Soamarat Vilaiyuk: None declared, Gaëlle Chédeville: None declared, Chris Pruunsild: None declared, Pekka Lahdenne: None declared, Nicolino Ruperto Grant/research support from: The Gaslini Hospital, where NR works as full-time public employee, has received contributions (> 10.000 USD each) from the following industries in the last 3 years: BMS, Eli-Lilly, GlaxoSmithKline, F Hoffmann-La Roche, Janssen, Novartis, Pfizer, Sobi. This funding has been reinvested for the research activities of the hospital in a fully independent manner, without any commitment with third parties., Consultant for: Received honoraria for consultancies or speaker bureaus (< 10.000 USD each) from the following pharmaceutical companies in the past 3 years: Ablynx, AbbVie, Astrazeneca-Medimmune, Biogen, Boehringer, Bristol-Myers Squibb, Eli-Lilly, EMD Serono, GlaxoSmithKline, Hoffmann-La Roche, Janssen, Merck, Novartis, Pfizer, R-Pharma, SanofiServier, Sinergie, Sobi and Takeda., Speakers bureau: Received honoraria for consultancies or speaker bureaus (< 10.000 USD each) from the following pharmaceutical companies in the past 3 years: Ablynx, AbbVie, Astrazeneca-Medimmune, Biogen, Boehringer, Bristol-Myers Squibb, Eli-Lilly, EMD Serono, GlaxoSmithKline, Hoffmann-La Roche, Janssen, Merck, Novartis, Pfizer, R-Pharma, SanofiServier, Sinergie, Sobi and Takeda., Angelo Ravelli Grant/research support from: Angelini, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Novartis, Pfizer, Reckitt Benkiser, and Roche, Consultant for: Angelini, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Novartis, Pfizer, Reckitt Benkiser, and Roche, Speakers bureau: Angelini, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Novartis, Pfizer, Reckitt Benkiser, and Roche, Alessandro Consolaro Grant/research support from: AbbVie, Pfizer,